Ginsenoside Rb1 Ameliorated Bavachin-Induced Renal Fibrosis via Suppressing Bip/eIF2α/CHOP Signaling-Mediated EMT - Ni, Yu-Hao; Deng, Hui-Fang; Zhou, Lei; Huang, Cong-Shu; Wang, Ning-Ning; Yue, Lan-Xin; Li, Gao-Fu; Yu, Hui-Jing; Zhou, Wei; Gao, Yue (Frontiers in Pharmacology, 2022)
The nephrotoxicity of Fructus Psoraleae, an effective traditional Chinese medicine for vitiligo treatment, has been reported. As one of the main toxic components in Fructus Psoraleae, bavachin (BV) was considered to be related with Fructus Psoraleae-caused adverse outcomes, but the direct evidence and molecular mechanism underlying BV-induced nephrotoxicity are not well elucidated. Therefore, this study was designed to confirm whether BV would cause toxic effects on kidney and explore the possible mode of action. Our results demonstrated that 21-day’s treatment with 0.5 μM BV indeed caused obvious renal fibrosis in zebrafish kidney. Obvious E- to N-cadherin switch and the expressions of proteins promoting epithelial-mesenchymal transition (EMT) were observed in BV-treated human renal tubular epithelia and zebrafish kidney. Besides, elevated reactive oxygen species (ROS) levels and Bip/eIF2α/CHOP-mediated endoplasmic reticulum (ER) stress and the unfolded protein response (UPR) were caused by BV, both of which could be reversed by ROS scavenger N-Acetyl-L-cysteine (NAC). Also, blocking ER stress-caused cytoplasmic Ca2+ overload with 4-PBA notably alleviated BV-induced alterations in key molecular events related to EMT and renal fibrosis. Furthermore, of the natural compounds subjected to screening, ginsenoside Rb1 significantly down-regulated BV-induced ER stress through inhibiting ROS generation and following the activation of Bip/eIF2α/CHOP signaling in HK2 cells. Subsequently, BV-triggered EMT and renal fibrosis were both ameliorated by ginsenoside Rb1. In summary, our findings suggested that BV-induced ROS promoted the appearance of EMT and renal fibrosis mainly via Bip/eIF2α/CHOP-mediated ER stress. This ER stress-related toxic pathway might be a potential intervention target for BV-caused renal fibrosis, and ginsenoside Rb1 would be a promising drug against BV- or Fructus Psoraleae-induced nephrotoxicity.